Signaling metabolite L-2-hydroxyglutarate activates the transcription factor HIF-1α in lipopolysaccharide-activated macrophages - Cloonan, Suzanne; O'Neill, Luke (My University, 2022)
Activated macrophages undergo metabolic reprogramming, which not only supports their energetic demands but also allows for the production of specific metabolites that function as signaling molecules. Several Krebs cycles, or Krebs-cycle-derived metabolites, including succinate, α-ketoglutarate, and itaconate, have recently been shown to modulate macrophage function. The accumulation of 2-hydroxyglutarate (2HG) has also been well documented in transformed cells and more recently shown to play a role in T cell and dendritic cell function. Here we have found that the abundance of both enantiomers of 2HG is increased in LPS-activated macrophages. We show that L-2HG, but not D-2HG, can promote the expression of the proinflammatory cytokine IL-1β and the adoption of an inflammatory, highly glycolytic metabolic state. These changes are likely mediated through activation of the transcription factor hypoxia-inducible factor-1α (HIF-1α) by L-2HG, a known inhibitor of the HIF prolyl hydroxylases. Expression of the enzyme responsible for L-2HG degradation, L-2HG dehydrogenase (L-2HGDH), was also found to be decreased in LPS-stimulated macrophages and may therefore also contribute to L-2HG accumulation. Finally, overexpression of L-2HGDH in HEK293 TLR4/MD2/CD14 cells inhibited HIF-1α activation by LPS, while knockdown of L-2HGDH in macrophages boosted the induction of HIF-1α-dependent genes, as well as increasing LPS-induced HIF-1α activity. Taken together, this study therefore identifies L-2HG as a metabolite that can regulate HIF-1α in macrophages.
Keywords: macrophages; Krebs cycles; L-2-hydroxyglutarate; Interleukin 1β (IL-1β); Inflammation; Glycolysis; Hypoxia-inducible factor (HIF); Immunometabolism